2019
DOI: 10.1371/journal.pone.0216643
|View full text |Cite
|
Sign up to set email alerts
|

Unpleasant meditation-related experiences in regular meditators: Prevalence, predictors, and conceptual considerations

Abstract: So far, the large and expanding body of research on meditation has mostly focussed on the putative benefits of meditation on health and well-being. However, a growing number of reports indicate that psychologically unpleasant experiences can occur in the context of meditation practice. Very little is known about the prevalence and potential causes of these experiences. The aim of this study was to report the prevalence of particularly unpleasant meditation-related experiences in a large international sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(100 citation statements)
references
References 69 publications
1
97
1
1
Order By: Relevance
“…All except 3 of the observational studies (88, 90, 94) employed quantitative methods, and its two most recent reports consisted of large surveys that accounted for 58% of the total sample size. (12, 13) The studies employed a wide variety of meditation techniques (see Table 1), though the majority used either mindfulness or mindfulness‐based interventions (MBIs) (61; 71%), or transcendental meditation (14; 16%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All except 3 of the observational studies (88, 90, 94) employed quantitative methods, and its two most recent reports consisted of large surveys that accounted for 58% of the total sample size. (12, 13) The studies employed a wide variety of meditation techniques (see Table 1), though the majority used either mindfulness or mindfulness‐based interventions (MBIs) (61; 71%), or transcendental meditation (14; 16%).…”
Section: Resultsmentioning
confidence: 99%
“…Within the psychotherapeutic literature, there is growing evidence that psychological treatments can be associated with AEs (13) with estimates ranging from 3% to 10% of patients who have become worse following psychotherapy (14). Similar findings have been reported for physical relaxation, which may in some individuals stimulate an increase in anxiety, an adverse event documented as ‘relaxation‐induced anxiety’ (15).…”
Section: Introductionmentioning
confidence: 99%
“…No financial compensation for participation was offered. A subsample of the current sample has previously been utilised to answer unrelated and non-overlapping research questions regarding unpleasant meditation-related experiences (Schlosser et al 2019).…”
Section: Methodsmentioning
confidence: 99%
“…68 A similar study was conducted by Schlosser et al (2019) highlighting the unpleasant meditation experiences among the regular practitioners. 69 Anderson et al (2018) in their work also explored the importance of studying the negative effects associated with meditation practices. 70 Moreover, some studies have also indicated the potential harmful effects of yoga and meditation practices in some psychological disorders such as clinical or sub-clinical epilepsy highlighting the increased incidence of epileptic seizures post meditation practice.…”
Section: Complementary Therapies For Stress Related Neuropsychiatric mentioning
confidence: 99%